(untitled) (Jurnal Kemanusiaan, 2019)
This study was conducted to enhance the level of creativity among students from the School of Education, Universiti Teknologi Malaysia by using e-learning. The main purpose of this study is to probe into the effectiveness of e-learning developed by the researchers for enhancing creativity. This study also look into how the learning process of creative thinking takes place among higher institutions students. The e-learning uses has been developed using the integration of Problem-Based Learning methods and creativity problem solving model (CPS). The samples are undergraduate students from the Faculty of Education who was sampled using purposive sampling technique. This is a pre-experimental study using quantitative and qualitative approach where students answer 6 items for the pre-test before receiving the intervention and later answering the open-ended question for the post-test. The reliability of the instrument was measured using internal consistency technique. The minimum Cronbach Alpha value is set to be at 0.6. The time session of preliminary study was recorded and will be used during the actual study. To obtain the qualitative data, students had to discuss in the forum that will developed in e-learning to observe their learning analytic data. This study is expected to produce a creativity learning framework for tertiary education students.